Enhancing Vigor of Cucumber (Cucumis sativus L.) Seeds Through Osmo-priming - Pradana, Adhitya Vishnu; Anugrah, Mertya; A'yunin, Qurrotu; Prayogi, Adi Noor; Togatorop, Eny Rolenti (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2025)
Cucumber production relies heavily on high-quality seeds, yet prolonged storage often leads to a significant decline in seed vigor and viability, characterized by reduced germination and non-uniform growth. To address this challenge, invigoration techniques through seed priming offer a promising solution to revitalize aged seeds, which also aligns with global sustainability efforts in preserving genetic resources and ensuring food security. This study aimed to evaluate the effectiveness of various invigoration treatments in enhancing the viability and vigor of expired cucumber seeds from different storage periods. The research utilized a factorial split-plot design with two factors, consisting of invigoration treatments (Control, KH₂PO₄, PEG, and Distilled Water) and storage periods (9 years, 7 years, and 5 years). The variables observed included radicle emergence (RE) at 24 and 48 hours, germination capacity, percentage of abnormal seedlings, and vigor index. The results showed that all invigoration treatments significantly improved seed performance compared to the control. The KH₂PO₄ treatment was the most effective for rapid improvement within 24 hours, showing a strong correlation (R=0.99) with increased vigor and a reduction in abnormal seedlings (R=0.85). However, distilled water showed the best performance for 48-hour RE, particularly when applied to 5-year stored seeds, reaching an 88% germination rate and the highest vigor index of 80%. In conclusion, invigoration is a viable method to restore the quality of aged seeds, with KH₂PO₄ and distilled water being recommended for optimizing the performance of specific seed lots. Future studies could further explore the field establishment of these invigorated seeds under diverse environmental stress conditions.